RETRACTED: Increasing interpersonal trust through divergent thinking - Sellaro, Roberta; Hommel, Bernhard; de Kwaadsteniet, Erik W.; van de Groep, Suzanne; Colzato, Lorenza S. (Frontiers in Psychology, 2014)
Interpersonal trust is an essential ingredient of many social relationships but how stable is it actually, and how is it controlled? There is evidence that the degree of trust into others might be rather volatile and can be affected by manipulations like drawing attention to personal interdependence or independence. Here we investigated whether the degree of interpersonal trust can be biased by inducing either a more integrative or a more cognitive-control mode by means of a creativity task requiring divergent or convergent thinking, respectively. Participants then performed the Trust Game, which provides an index of interpersonal trust by assessing the money units one participant (the trustor) transfers to another participant (the trustee). As expected, participants transferred significantly more money to the trustee after engaging in divergent thinking as compared to convergent thinking. This observation provides support for the idea that interpersonal trust is controlled by domain-general (i.e., not socially dedicated) cognitive states.